O desenho digital e as paisagens patrimoniais. Convento da Madre Deus de Monchique, no Porto - Cruz, Tiago Trindade (CEM – Cultura, Espaço & Memória, 2021)
This article is part of a broader reflection on the digital drawing and new research methodologies in the History of Architecture. Aiming to reflect on the concept of Heritage Landscape, it starts from the old monastic structure of Monchique, in the city of Porto, as an experimental laboratory for architectural and urban research. It is known that digital technology makes it possible to reconstruct elements from other eras, whose time has transformed or disappeared. In this context, and using digital drawing, the recognition of the built heritage and urban structures is sought through a synchronic and diachronic interpretation, attentive to the different historical periods and their specificities.